Designing Work Tools That Potentially Reduce Risk Of Musculoskeletal Disorders In Neutral Amine Filling Activities - Kusmasari, Wyke; Pamungkas, Fadil; Wajdi, Farid (Jurnal Ilmiah Teknik Industri, 2025)
Petrochemical is a manufacturing company that uses automatic machines in its production process. However, there is also a production process that is carried out manually, namely the activity of filling 25L of neutral amine chemicals four times a day. Unergonomic work postures when filling neutral amine chemicals often cause musculoskeletal disorders such as pain in the waist and back. Based on the Nordic Questionnaire, data on the prevalence of musculoskeletal disorders in the last 12 months showed complaints in the right elbow, upper back, lower back and left knee had a percentage of 100% and in the last 7 days in the lower back had a percentage of 100%. This is evidenced by the examination of 100 screenshots of work posture images when filling neutral amine chemicals, which resulted in a RULA score of 58% for high risk and a REBA score of 59% for moderate risk. From the calculation results, the average of the five workers was a QEC assessment of 59% and a JSI assessment of 9.75. Based on QFD, it produces 6 target specifications, which are AODP pump, anthropometric data of the pelvic height dimension, palm width dimension, forward hand grip distance dimension, measuring cup lid and pipe interconnection. Based on the simulation results, there was a decrease in the score by 3 points, which proves that the design of neutral amine filling work tools has the potential to reduce the risk of musculoskeletal disorders.